Comparative industrial & employment relations (Sage, 1995)
This broad-ranging textbook provides a comprehensive introduction to industrial relations and employment relations in the wider economic, technological and political context. Transcending any specific national setting, it compares industrial and employment relations in different countries, and identifies the elements of commonality across the range of national systems. Throughout, employment relations are set within the framework of the overall relationship between firms, markets, interest organizations and governments. Comparative Industrial and Employment Relations will be essential reading for students of industrial relations and for those involved in human resource management and personnel management seeking a wider perspective on the context of industrial and employment relations.